Analysis of phthalates in foods by using gas chromatography mass spetrometry (GC-MS) / Tan Poh Wei - Tan, Poh Wei (2014)
Migration of phthalates from food packaging into food has caused exposure of human on these compounds. Also, these compounds may cause adverse effect on human and thus, identification and quantification of these compounds in food become more particular. Simple and rapid methods have been developed for the simultaneous determination of six phthalate compounds in the food samples including drinking water, milk, cereal and instant noodles by using gas chromatography mass spectrometry (GC-MS). The six phthalate compounds been examined were dimethylphthlate (DMP), diethylphthalate (DEP), dibutylphthalate (DBP), benzyl butyl phthalate (BBP), diethylhexylphthalate (DEHP) and dioctylphthlate (DNOP). For both liquid and solid samples, extractions were done by using solvent n-hexane. For liquid samples, the limit of detection (LOD) and limit of quantification (LOQ) were 3.3 μg/L and 10 μg/L respectively. While for solid samples, the LOD and LOQ were 0.33 mg/kg and 1 mg/kg respectively. The sample spiked recoveries were in the range of 72.9-124.9 % with relatively low relative standard deviation (RSD) that was below 3.30 %.